2022
DOI: 10.1002/hbm.25857
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of network centrality and gray matter microstructure using multi‐session brain stimulation and memory training

Abstract: Neural mechanisms of behavioral improvement induced by repeated transcranial direct current stimulation (tDCS) combined with cognitive training are yet unclear. Previously, we reported behavioral effects of a 3‐day visuospatial memory training with concurrent anodal tDCS over the right temporoparietal cortex in older adults. To investigate intervention‐induced neural alterations we here used functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) datasets available from 35 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 109 publications
0
9
1
Order By: Relevance
“…Simultaneous tDCS-fMRI application in proof-of-principle studies revealed changes in local activity and functional connectivity (temporally coherent activity between brain regions) that predicted behavioral performance gains 33 35 . Functional connectivity modulations in response to repeated training sessions may even reflect network level reorganizations, promoting longer-lasting neural plasticity 4 , 36 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous tDCS-fMRI application in proof-of-principle studies revealed changes in local activity and functional connectivity (temporally coherent activity between brain regions) that predicted behavioral performance gains 33 35 . Functional connectivity modulations in response to repeated training sessions may even reflect network level reorganizations, promoting longer-lasting neural plasticity 4 , 36 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In the current paper, we used DTI acquired before and after the intervention for individual fiber tractography and quantification of white matter microstructure. Further, DTI allowed us to examine whether microstructural properties in the stimulation target would change due to the intervention as suggested previously 38 . The investigation of microstructural plasticity markers was complemented by resting-state functional magnetic resonance imaging (rs-fMRI) to analyze functional synchrony modifications within the targeted (frontoparietal) network.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous tDCS-fMRI application in proof-of-principle studies revealed changes in local activity and functional connectivity (temporally coherent activity between brain regions) that predicted behavioral performance gains 16,17,18 . Functional connectivity modulations in response to repeated training sessions may even re ect network level reorganizations, promoting longer-lasting neural plasticity 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…For individual ber tractography and quanti cation of white matter microstructure, we used DTI acquired before and after the intervention. Further, DTI allowed us to examine whether microstructural properties in the stimulation target would change due to the intervention as suggested previously 22 . The investigation of microstructural plasticity markers was complemented by resting-state functional magnetic resonance imaging (rs-fMRI) to analyze functional synchrony modi cations within the targeted (fronto-parietal) network.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, few studies have examined the aftereffects of tDCS on these neurophysiological measures immediately after the end of WMT, typically at the end [36,39] or one day after the last training session [4,[32][33][34]. A recent study utilizing resting-state functional magnetic resonance imaging (fMRI) found improved brain network processing efficiency with 3-day of tDCS+WMT one day after training [40]. However, no significant effects of tDCS on brain activity were found in a 3day WMT+tDCS study that quantified long-term neurobehavioral effects using ERPs at one month [38].…”
Section: Introductionmentioning
confidence: 99%